2011
DOI: 10.1111/j.1365-2133.2011.10554.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen saturation and perfusion changes during dermatological methylaminolaevulinate photodynamic therapy

Abstract: Background: Methyl-aminolevulinate photodynamic therapy (MAL-PDT) is a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
0
17
0
2
Order By: Relevance
“…Our previous studies have also observed significant interpatient variations as once again observed here. This is thought to be the result of numerous external factors (especially the overall health of the patient), which may potentially alter the capacity for photochemical reactions and therefore the relationship between PpIX photobleaching and oxygen saturation [24]. For example, the age, body temperature and general well being of a patient can affect their tissue oxygenation status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have also observed significant interpatient variations as once again observed here. This is thought to be the result of numerous external factors (especially the overall health of the patient), which may potentially alter the capacity for photochemical reactions and therefore the relationship between PpIX photobleaching and oxygen saturation [24]. For example, the age, body temperature and general well being of a patient can affect their tissue oxygenation status.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study which used an ORS system to monitor the oxygen saturation of 60 patients during standard MAL-PDT, a significant decrease was observed following the first minute of irradiation [24]. This decrease was attributed to the consumption of oxygen during the photochemical reactions.…”
Section: Discussionmentioning
confidence: 99%
“…We recognize that there is no generally accepted independent evidence for this effect; measurements of blood flow during PDT have been inconclusive. [16][17][18][19][20] Although this reduction in perfusion has a significant effect on observed fluorescence, the effect on singlet oxygen dose is relatively small as shown in Fig. 6 in which the results of Fig.…”
Section: Treatment Simulationsmentioning
confidence: 95%
“…Both skin autofluorescence and PpIX fluorescence were measured. Since optical properties are known to change during PDT [37][38][39][40], we measured PpIX fluorescence at various time-points during PDT.…”
Section: Introductionmentioning
confidence: 99%